2023
DOI: 10.3390/cryst13060899
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic Investigation of Binary Mixtures of Liquid Crystal Molecules with Different Mesogenic Architectonics

Abstract: Different binary phase diagrams, made from two differently substituted three-rings azo/ester and azomethine/ester compounds of the same terminal alkoxy side chain of six carbons, as opposed to the other terminal polar substituent, which can either donate electrons or withdraw electrons including H. The thermal behavior of the prepared derivatives was investigated by differential scanning calorimetry and phases identified by polarized optical microscope. The first group of the binary mixtures was made from late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Several researchers [ 12 , 14 , 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] have demonstrated that computational studies are a great tool for designing novel materials. Molecular orbital energies, the frontier molecular orbital energy difference, and the molecular geometries of the investigated LC compounds must all be stimulated to produce novel compounds with appropriate optical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers [ 12 , 14 , 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] have demonstrated that computational studies are a great tool for designing novel materials. Molecular orbital energies, the frontier molecular orbital energy difference, and the molecular geometries of the investigated LC compounds must all be stimulated to produce novel compounds with appropriate optical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high performance and accurate results, density functional theory (DFT) is widely acknowledged as an appropriate instrument for making these predictions [ 39 ]. In addition, one of our research areas focuses on theoretical calculations of molecular geometry that impact thermal properties and links them to experimental data [ 12 , 33 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation